Psi Effect or Sensory Leakage: Scrutinizing the Ball Selection Test - Ertel, Suitbert (Journal of Scientific Exploration, 2013)
The Ball Selection Test (BST) (Ertel 2004) is a simple, entertaining, forced-choice test for assessing psi ability. Fifty ping-pong balls, each with a number from 1 to 5 written on its surface, are used as targets. After the balls are shaken in an opaque bag, a participant blindly draws out one ball while attempting to call out the number written on it. If the number on the ball matches the participant's call, the trial is scored as a "hit." Because the numbers are equally distributed across the 50 balls, the mean chance expectation (MCE) for a hit is 20%. Two earlier experiments had suggested that sensory cues such as tactile cues from the written numbers or temperature cues from recently selected balls could not account for successful BST performance. The experiment reported in this article further examines this artifactual concern by comparing hit rates on the standard BST procedure with those on a modified version of the BST that required participants to wear blindfolds and gloves. Hit rates were significantly above chance on both procedures and virtually identical to each other, strongly confirming that sensory leakage cannot account for above-chance performance on the BST. The BST has several other features that make it uniquely suited for screening psi abilities. Keywords: Ball Selection Test-paranormal-psi-sensory leakage-ESP <!--[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->